Seroreversion of positive anti‐hepatitis C virus antibodies in left ventricular assist device recipients: Now you see them, now you don't. Issue 8 (28th February 2019) - Sims, Daniel B.; Kataria, Rachna; Rangasamy, Sabarivinoth; Jorde, Ulrich P.
Abstract: The clinical significance of positive anti‐hepatitis C virus (anti‐HCV) antibody tests in recipients of left ventricular assist devices remains unclear. In light of emerging evidence suggesting the possibility of persistent low‐level HCV infection in patients with positive anti‐HCV antibody test but negative HCV ribonucleic acid, it is very important to distinguish the truly false positive HCV antibodies, in recipients of continuous flow left ventricular assist devices, from those suggestive of a prior clinically resolved infection or one where a low‐level viremia may have persisted. We conducted a retrospective analysis of left ventricular assist device recipients at our institution. While the total incidence of positive HCV antibody with concomitantly negative HCV ribonucleic acid test (19.2%) was in keeping with the incidences reported in prior cross‐sectional studies, we longitudinally followed our patients and observed a 100% seroreversion. Seroreversion, which has not been reported in other studies, occurred either during continued left ventricular assist device support (10 out of 26) or after heart transplant (7 out of 26). Hundred percent seroreversion strongly suggested that the anti‐HCV antibodies were truly false positive.